The Effectiveness of Textbook Character Education-Based in Madrasah Aliyah at Gorontalo - Mantau, Burhanudin Abdul Karim (Al-Lisan: Jurnal Bahasa, 2023)
The objective of this study is to find out the effectiveness of character education in Madrasah Aliyah at Gorontalo. Four Madrasah Aliyah are used as research settings such as MAN Insan Cendekia, Madrasah Aliyah al-Khairaat, Madrasah Aliyah Muhammadiyah, and Madrasah Aliyah al-Yusra. The number of subjects in this study was 221 students divided into two groups control groups as many as 114 students and experimental groups of 107 students. In addition, researchers also involved four lecturers of the poetry appreciation universities. This study used an experimental method with an independent t-test model that compares the difference between the pre-test and post-test values ​​of the control class and the experimental class. The result of the analysis shows that the average score of the experimental group is 15.68 and the control group average is 10.86. Then an independent t-test result of the t-count is 5.087 along with a significance value of 0.000. Due to the significance of 0.000 <0.05, the Ho was rejected and there was a significant difference between the pretest and the post-test, the experimental group and the control group. Thus, the character-based education is effectively used in higher education.